2014
DOI: 10.1002/dta.1628
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the designer benzodiazepine diclazepam and preliminary data on its metabolism and pharmacokinetics

Abstract: Designer benzodiazepines, first offered in online shops selling 'research chemicals' in 2012, provide an attractive alternative to prescription-only benzodiazepines as they are readily available over the Internet at a low price. However, as data regarding pharmacokinetic parameters, metabolism, and detectability in biological fluids are limited, they present a challenge for forensic laboratories. Most recently, diclazepam (other names: 2-chlorodiazepam, Ro 5-3448 or 7-chloro-5-(2-chlorophenyl)-1-methyl-1,3-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 13 publications
1
57
2
Order By: Relevance
“…[10] Cross-reactivity of etizolam in the CEDIA assay was found to be 144 %, which differed from our previous finding of 237%, [11] although both values were determined at about the same concentrations. [10] Cross-reactivity of etizolam in the CEDIA assay was found to be 144 %, which differed from our previous finding of 237%, [11] although both values were determined at about the same concentrations.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…[10] Cross-reactivity of etizolam in the CEDIA assay was found to be 144 %, which differed from our previous finding of 237%, [11] although both values were determined at about the same concentrations. [10] Cross-reactivity of etizolam in the CEDIA assay was found to be 144 %, which differed from our previous finding of 237%, [11] although both values were determined at about the same concentrations.…”
Section: Resultscontrasting
confidence: 88%
“…[6][7][8] However, immunoassays still hold their place in routine high-throughput urine drug screening and it has been observed that the new abused drugs may also cross-react in the existing commercial reagents. [10] In CEDIA, etizolam showed 237% cross-reactivity. [9] Knowledge about the detectability of designer benzodiazepines in commercial benzodiazepine immunoassays is limited.…”
Section: Introductionmentioning
confidence: 98%
“…4 mm column (Thermo Fisher Scientific, Idstein, Germany) using our routine screening gradient, as previously described. 4 mm column (Thermo Fisher Scientific, Idstein, Germany) using our routine screening gradient, as previously described.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…1 Since the appearance of pyrazolam on the drug market in 2012, 2 internet shops continue to offer either modifications of popular, licensed benzodiazepines or metabolites thereof. 4,5 Appearance of highly potent triazolo-compounds such as flubromazolam as pure powder may lead to the abuse of such compounds in a drug-facilitated crime context and can easily lead to severe intoxications due to dosing errors. 3 In particular, offer of metabolites [eg, norflunitrazepam ('fonazepam') and 3-hydroxyphenazepam] or designer benzodiazepines metabolizing to licensed benzodiazepines (eg, diclazepam and cloniprazepam) pose challenges for correct interpretation of analytical findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation